Effect of Depot Medoxyprogesterone Acetate on Immune Functions and Inflammatory Markers of HIV-Infected Women. (1st February 2016) - Weinberg, Adriana; Park, Jeong-Gun; Bosch, Ronald; Cho, Alice; Livingston, Elizabeth; Aweeka, Fran; Cramer, Yoninah; Watts, D. Heather; Luque, Amneris E.; Cohn, Susan E.
Abstract : Objectives: Depot medroxyprogesterone acetate (DMPA) was associated with increased HIV transmission and accelerated disease progression in untreated women. The potential underlying mechanisms include immune modulation. We evaluated the effect of a single DMPA injection on cell-mediated immunity (CMI), T-cell activation, T-cell regulation (Treg), and inflammation in HIV-infected women on combination antiretroviral regimen (cART). Methods: Women with HIV plasma RNA⩽ 400 copies per milliliter on stable cART received DMPA and had immunologic and medroxyprogesterone acetate (MPA) measurements at baseline, 4 weeks [peak MPA concentration (Cmax )], and 12 weeks [highest MPA area under the concentration curve]. Results: At baseline, among 24 women with median age of 32 years and 622 CD4 + cells per microliter, ≥68% had HIV, varicella-zoster virus, phytohemagglutinin A and CD3/CD28 CMI measured by lymphocyte proliferation, and/or IFNγ/IL2 dual-color fluorospot. CMI did not significantly change after DMPA administration except for a 1.4-fold increase in IL2/IFNγ varicella-zoster virus fluorospot at week 12. T-cell activation decreased after DMPA administration, reaching statistical significance at week 12 for CD4 + CD25+%. Treg behaved heterogeneously with an increase in CD8+FOXP3+% at week 4 and a decrease in CD4+IL35+% at week 12. There was a decrease in TGFβ at week 12 and no other changes in plasma biomarkers. Correlation analyses showed that high MPA Cmax and/or area under the concentration curve were significantly associated with increases of IFNγ HIV enzyme-linked ImmunoSpot, CD4+IL35+%, and CD4+TGFβ+% Treg and decreases of plasma IL10 from baseline to weeks 4 and/or 12. Conclusions: A single dose of DMPA did not have immune-suppressive or pro-inflammatory effects in HIV-infected women on cART. Additional studies need to assess the effect of multiple doses.